Diseño e implementación de un sistema de generación eléctrico solar y eólico para una casa comunal ubicada en el sector san isidro alto perteneciente a la parroquia de Aláquez del cantón Latacunga, provincia de Cotopaxi en el periodo 2014-2015 - Iturralde Ayala, José Roberto (2015)
The main objective research is to design and implement a wind-solar hybrid power generation system to supply the demand in a community house, which will be obtained by using the natural energy resources such as wind and sun. To the design of hibrid genertion system, it was choosen the community house located in San Isidro Alto-Aláquez, in Cotopaxi province. The data obtained from solar radiation and the wind speed during 24 hours, it was collected from Ecuadorian Construction Standards and the International Airport which obtained an average solar insolation of 4320Wh / m2 in the day and an average of heliophany 4.3 hours in day and average wind speed of 5 m / s in the day....